VOCATIONAL TECHNICAL EDUCATION APPLICATION IN MODULAR TECHNOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article outlines the role of modular teaching technology in training specialists, competitive in todays globalization and information society, developing at a fast pace of the economy as part of a competent approach to practice and theory of education.